The Impact of Blended Learning on Teaching English for Vocational Purposes - Lesiak-Bielawska, Elżbieta Danuta (Glottodidactica, 2012)
The one-group experiment attempted to investigate the impact of blended learning on teaching English for Vocational Purposes (EVP). To maximize its internal and external validity, methodology of triangulation was employed. The results obtained indicate considerable progress and statistically significant differences between the pre-treatment and post-treatment scores in the overall acquisition of technical terminology and in the area of vocational vocabulary learned productively.